Instruments of health literacy used in nursing studies with hypertensive elderly - Ana Larissa Gomes Machado; Francisca Elisângela Teixeira Lima; Tahissa Frota Cavalcante; Thelma Leite de Araújo; Neiva Francenely Cunha Vieira
This study aimed to analyze nursing research regarding the instruments used to evaluate health literacy in elderly hypertensive patients. This is an integrative literature review done in the databases LILACS, PubMed, CINAHL, Scopus, and Cochrane, in June 2013. The articles, electronically available, were selected for full-text review by nurses, who assessed health literacy of elderly with hypertension. Eight studies were selected for analysis and four different instruments were used in the research. The instruments were developed according to a methodology and they were all designed to evaluate the abilities of elderly regarding reading, numeracy, pronunciation and recognition of some health-related words. The nursing research analyzed in this study revealed the gaps in care related to measures aimed to increase patient's involvement in decision-making. Also, the instruments used for measuring health literacy showed limitations, and there is no gold standard test.